The Benefits of Separating Rail Infrastructure from Operations - Thompson, Louis S. (World Bank, Washington, DC, 2012)
The author offers a number of reasons for separating rail infrastructure from operations: to reduce unit costs, to create intrarail competition, to better focus on the services to be provided, to clarify public policy, and to strike a better balance between the roles of the public and private sectors. Moreover, recent experience with "negative" concessions, in which the private sector provides public services (based on competition to provide the service and in return for compensation), is adding another dimension to the "public vs. private" debate. In this sense separating infrastructure allows new approaches to the problem of meeting public responsibilities. Concessioning programs in Argentina, Sweden, and the United Kingdom define the broad alternatives in rail infrastructure separation. The two main challenges for separation are capacity management and pricing policies. While it is true that infrastructure separation is messy and expensive, it will be a small price to pay if "fragmentation" offers a better fit for consumers.